WOMEN, THE SIN OF ABORTION AND ABSOLUTION: FEMINIST THEOLOGICAL QUESTIONS - Abraham, Kochurani (Asian Horizons, 2016)
Catholics worldwide have begun the Year of Mercy with openness and freedom as mercy is a desirable human experience bestowing healing and wholeness. All the same, the letter of Pope Francis that authorizes priests around the world to forgive women of the “sin of abortion” during the year of mercy raises critical concerns from the standpoint of women’s experience. This short article looks into the complexities underlying women’s experience of abortion particularly in the sociocultural context of Asia that is inscribed by patriarchy. It problematizes the positioning of women in catholic theology as vulnerable recipients of mercy and interrogates critically the catholic pastoral praxis that is blind to the responsibility of the man/husband on questions relating to abortion and its consequences. Finally, using the key of feminist theological hermeneutics, it intends to take the discourse on the ‘sin of abortion,’ pro-life and pro-choice to a broader framework of life in its connectedness and relatedness.